Studies on cerebral protection of digoxin against hypoxic–ischemic brain damage in neonatal rats. Issue 12 (17th August 2016) - Peng, Kaiwei; Tan, Danfeng; He, Miao; Guo, Dandan; Huang, Juan; Wang, Xia; Liu, Chentao; Zheng, Xiangrong
Abstract : Hypoxic–ischemic brain damage (HIBD) is a major cause of neonatal acute deaths and chronic nervous system damage. Our present study was designed to investigate the possible neuroprotective effect of digoxin-induced pharmacological preconditioning after hypoxia–ischemia and underlying mechanisms. Neonatal rats were assigned randomly to control, HIBD, or HIBD+digoxin groups. Pharmacological preconditioning was induced by administration of digoxin 72 h before inducing HIBD by carotid occlusion+hypoxia. Behavioral assays, and neuropathological and apoptotic assessments were performed to examine the effects; the expression of Na + /K + ATPase was also assessed. Rats in the HIBD group showed deficiencies on the T-maze, radial water maze, and postural reflex tests, whereas the HIBD+digoxin group showed significant improvements on all behavioral tests. The rats treated with digoxin showed recovery of pathological conditions, increased number of neural cells and proliferative cells, and decreased number of apoptotic cells. Meanwhile, an increased expression level of Na + /K + ATPase was observed after digoxin preconditioning treatment. The preconditioning treatment of digoxin contributed toward an improved functional recovery and exerted a marked neuroprotective effect including promotion of cell proliferation and reduction of apoptosis after HIBD, and the neuroprotective action was likely associated with increased expression of Na + /K + ATPase.